Family caregivers' experiences of caring for neonates undergoing enterostomy in China: A qualitative study - Zhi Hong Ni; Sheng Ding; Jin Hua Wu; Fang Wang (Wiley, 2023)
Abstract Aim To describe the nursing experiences and care needs of family caregivers caring for neonates with enterostomies in China. Design A qualitative study. Methods We conducted semi‐structured interviews with family caregivers who care for neonates undergoing enterostomy. Family caregivers were selected using a purposive sampling method from three children's hospitals until no new data were generated (N = 26). Data analysis applied the thematic analysis method. The caregivers' experiences were described using qualitative content analysis. Results The experience of family caregivers was described as growing in adaptation, where five main themes emerged: (1) complex emotional responses; (2) uncertainty about everything; (3) lack of confidence, anxiety and helplessness; (4) eagerness for professional support; (5) active adaptation, gain‐harvest and gain‐growth. These findings increased understanding and added knowledge on this topic that is rarely studied in China. Healthcare authorities and professionals should recognize and understand the lives and situations of family caregivers (whose neonates undergo enterostomy) to better identify their difficulties and needs.